Occurrence of Haematococcus pluvialis Flotow emend. Wille in a small artificial pool on the university campus of the Collegium Biologicum in Poznań (Poland) - Burchardt, Lubomira; Balcerkiewicz, Stanisław; Kokociński, Mikołaj; Samardakiewicz, Sławomir; Adamski, Zbigniew (Biodiversity: Research and Conservation, 2006)
Haematoccocus pluvialis is a widely distributed unicellular green alga belonging to the order Volvocales and family Haematococcaceae. Its natural habitats include small, often temporary, continental and coastal rock pools, water holes and other small natural or artificial water habitats. It has been reported world-wide, but in Poland only a few cases of its occurrence have been noted in southern Poland. However, H. pluvialis was identified in a small artificial pool at Adam Mickiewicz University in Poznań during very hot and sunny days in July 2005. Because of these severe conditions only the resting hematocyst stage of this species was initially observed. This stage contained the red carotenoid pigment astaxanthin. Using confocal microscopy, large amounts of astaxanthin were observed in the central area of the resting cells. After transferring the hematocysts to culture media the flagellate macrozooid and palmella stages developed. The presence of H. pluvialis in this pool in the northwestern part of Poland supports the capability of this species to expand its distribution range over long distances.